Vocational High School Students’ Sense of Self-Efficacy and Test Anxiety Regarding Biology Learning - M. Serdar KÖKSAL (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Self-regulation perspective on motivation provides an important model to study on motivation in biologyeducation. Motivational part of the Pintrich’s model as one of the most studied models has self-efficacy andtest-anxiety factors as two dominant factors reflecting positive and negative sides of the model in terms ofnumber of relationship with other factors in the model. In the study, two hundred thirteen vocational highschool students were included and survey technique was used for examining the factors across grade level inthe study. Two subscales of MSLQ were applied to collect data. The data was analyzed by using MANOVAand Pearson-product moment correlation via SPSS 13. The results showed self-efficacy and test anxietyscores differed significantly between ninth and tenth graders. Again, they were correlated negatively at thesame levels.